Exomissiology: The Launching of Exotheology - Hoffmann, Thomas (Dialog, 2004)
The world's technologically advanced societies are actively engaged in space exploration. This includes locating possible planets supporting life and advancing earth's colonizing presence beyond the earth's atmosphere. Speculative (philosophical) theology has begun to engage the possibility of extra-terrestrial life through the study of exotheology. This article argues that exomissiology must inform and shape exotheology. Exomissiology affirms a “pluriverse”, rejects the privatization and reductionism of faith, adopts a systems worldview, commits to an expansive and relational community based on a radical understanding of both creation and the Trinity, clarifies a vision of hope, and, embraces the church as the “plausibility structure” of the gospel.